Spectrum of glucose-6-phosphate dehydrogenase (G6PD) mutations and trends in hemoglobin levels among adult dengue patients in Thailand - Supat Chamnanchanunt; Beatriz Aira C. Jacob; Vipa Thanachartwet; Varunee Desakorn; Natsamon Singha-art; Duangjai Sahassananda; Kamonwan Chamchoy; Naveen Eugene Louis; Muawiaa Ahmed Hamza; Nurriza Ab Latif; Syazwani Itri Amran; Henry A. F. Stephens; et al. (PLoS ONE, 2025)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in humans that may exacerbate clinical outcomes during viral infections such as dengue, particularly in regions where both conditions are endemic. This study aimed to characterize the spectrum of G6PD mutations and explore trends in hemoglobin levels among adult dengue patients in Thailand. Samples from 231 adult patients diagnosed with dengue were analyzed. G6PD deficiency was identified in 24 individuals (10.4%), while G6PD mutations were detected in 111 patients (48.1%). The most frequently observed mutations include a combination of synonymous and intronic mutations (c.1311C > T and c.1365-13T > C), compound mutation of G6PD Viangchan (c. 871G > A, c.1311C > T and c.1365-13T > C), and a deletion variant (c.486−34delT). Additionally, a novel variant, c.1439T > C, was identified and named “G6PD Phaya Thai”. Patients carrying G6PD mutations exhibited different hemoglobin level trends compared to those without mutations. Specifically, while hemoglobin levels increased from the febrile to critical phase in patients without mutations, a significant decline was observed in mutation carriers. Median hemoglobin levels differed significantly between the two groups during both the febrile and critical phases (p = 0.02 and p < 0.001, respectively). Biochemical and structural analyses of uncharacterized variants, G6PD Phaya Thai and G6PD Viangchan+Chinese-5, suggested structural instability as a possible mechanism for the observed deficiency. These findings highlight the need for further investigation into the potential role of G6PD variants in dengue-related anemia. Routine G6PD screening and continuous hemoglobin monitoring may help identify individuals at risk of hemoglobin decline and guide supportive care strategies in dengue-endemic regions.